PIECES Analysis and Effect of Fikri Karya Gemilang Website Design on Promotion System Using Waterfall Model - Anwardi; Anggi Ramadona; Misra Hartati; Tengku Nurainun; Ekie Gilang Permata (School of Industrial and System Engineering, Telkom University, 2020)
Promotion is one type of communication that is often used by marketers, as one element of the promotionalmix. The promotion process carried out by CV Fikri Karya Gemilang is a traditional promotion model,with direct visits without other alteratives. The promotion system still does not provide optimalperformance for the company's revenue. Based on data from the company, there is a decrease in jobs thatare not in accordance with the company's target and unreachable regional segmentation. This study usesthe PIECES method by analyzing the company's promotion system. This research proposes a websitedesign using the waterfall model and usability testing on the website with a total score of 0.72 whichmeans good, and the application of online media as an internet-based promotion media. This study alsolooked at the effect of the adoption of a traditional promotion system and the adoption of an internet-basedproposed promotion system using paired sample t-tests. Based on the PIECES analysis, it is found thatthere is a level of customer satisfaction with the application of a manual promotion system that is less thanoptimal, and the application of the proposed promotion system provides an increase in consumersatisfaction. Based on paired sample t-test, it can be concluded that the Sig (2-tailed) value of 0.0000015means that there is a significant difference between the application of the traditional promotion system andthe internet-based proposal promotion system.